PRINCIPLES OF FORMATION OF FINANCIAL STRATEGY OF THE COMPANY - Oleg M. Nedelko (Вестник Северо-Кавказского федерального университета, 2022)
The article deals theoretical approaches to the definition of the principles of financial strategy of the company, on the basis of their systematization of the author offers his version of the principles would guide the financial strategy of the entity.